The Comprehensive Analysis of Mangrove Vegetation in Penunggul Village, Pasuruan Regency, Indonesia - Dito Aditia; Karunia Setyowati Suroto; Kamila Munna; Helga Regita Safira (International Research & Development for Human Beings (IRDH), 2024)
This research aims to conceive the current condition of the mangrove vegetation community in Penunggul and proposes consideration of the attempt of maintaining the mangrove ecosystem in Penunggul. The primary data including species, density, dominance, and IVI (Important Value Index) are mined through a mangrove resource survey with vegetation analysis technique. Parameters for the study cover water quality including physics, chemical, tidal and soil quality parameters. Samples of the study are taken from three stations, Lawean river mouth, old fish ponds, and an area near the residential. The result of the study shows that Rhizophora mucronata dominates the growth in the research areas. The high scale of dominance and IVI indicates the important role of the species in the environment, such as producing organic materials and seedlings that contribute to the regeneration of mangrove habitats. Moreover, the parameter of water and soil quality shows an optimum scale for mangrove growth.